Measuring resilience is essential to understand it - Pimm, Stuart L.; Donohue, Ian; Montoya, José M.; Loreau, Michel (2019)
The terms sustainability, resilience and others group under the heading of ‘stability’. Their ubiquity speaks to a vital need to characterize changes in complex social and environmental systems. In a bewildering array of terms, practical measurements are essential to permit comparisons and so untangle underlying relationships.